The trajectory of crack users to the street situation in the perspective of family members - Seleghim, Maycon Rogério; Frari Galera, Sueli Aparecida (Investigación y Educación en Enfermería, 2019)
Objective. To understand the family experience regarding the trajectory of crack users for the street situation. Method. Qualitative study using the systemic approach as the theoretical referential and the narrative as methodological referential. We conducted interviews with eleven family members of crack users with street situation experience cared for at a community mental health service. We analyzed the interviews using the inductive content analysis technique. Results. The family members understood the trajectory of the crack users for the street situation from two perspectives. One before the street situation process, for which they described a problematic childhood, the presence of stressor traumas/ events, vulnerabilities in the family environment, and their family members’ encounter with the drug world. Moreover, another posterior to the street situation, for which they narrated the perception of alterations in the users, the discovery of crack use, the deepening of the individuals’ relationship with the streets, and the adoption of coping strategies. Conclusion. It was made evident that the family adopts an explicative model for the behavior of drug use and contact with the streets based on the life history of the crack user family member. How to cite this article: How to cite this article: Seleghim MR, Galera SAF. The trajectory of crack users to the street situation in the perspective of family members. Invest. Educ. Enferm. 2019; 37(2):e03.